2020
DOI: 10.1039/d0qo00848f
|View full text |Cite
|
Sign up to set email alerts
|

Stay positive: catalysis with 1,3,2-diazaphospholenes

Abstract: P–hydrido 1,3,2-diazaphospholenes (DAPs) are a class of nucleophilic molecular hydrides capable of addition to a variety of substrates. They can be turned over with terminal reductants and emerged over the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Building on our previous work 59 , we envisioned that diazaphospholenes of super hydricity 60 62 may provide a good chance to realize HDF of trifluoromethylalkenes via an S N 2’ path 63 . A preliminary attempt indicated that the reaction of α-trifluoromethyl-styrene 2a with diazaphospholene 1 primarily gave the hydrophosphination intermediate A .…”
Section: Resultsmentioning
confidence: 98%
“…Building on our previous work 59 , we envisioned that diazaphospholenes of super hydricity 60 62 may provide a good chance to realize HDF of trifluoromethylalkenes via an S N 2’ path 63 . A preliminary attempt indicated that the reaction of α-trifluoromethyl-styrene 2a with diazaphospholene 1 primarily gave the hydrophosphination intermediate A .…”
Section: Resultsmentioning
confidence: 98%
“…This feature might be exploited further in the context of diazaphospholene chemistry for organocatalysis. [40] We also monitored the NMR-scale reaction of 1 with a 1.5 M stock solution of dimethylamine, which led to a mere 7 % conversion to 7 after a few minutes at room temperature with no further conversion observed over time. The combined experimental and computational data suggest that a high activation barrier for reaction between the amine substrate and the distorted P(III) center under the chosen conditions may be responsible for the observed lack of complete proton transfer in case of the latter reaction as well as for the formation of 6 as a minor equilibrium product.…”
Section: Synthesis Of P(iiimentioning
confidence: 99%
“…1,3,2-Diazaphospholenes (DAPs) are heterocycles that contain a carbon–carbon double bond and two nitrogen atoms separated by a phosphorus atom. These compounds have been widely used as catalysts in organic synthesis, mainly due to the unique reactivity of P-hydrido substituted members of this family [ 121 ]. The most widely used protocol for their synthesis is a two-step process consisting of reduction of the 1,4-diaza-1,3-butadiene 272 with lithium or sodium to afford the corresponding dianion, which could react directly with PCl 3 or could be protonated first with triethylamine hydrochloride, and after that, react with PCl 3 to afford the respective P -chloro-1,3,2-diazaphospholene derivatives 273 .…”
Section: Synthesis Of Heterocycles Using 14-diaza-13-butadienesmentioning
confidence: 99%